Korelasi antara Keaktifan dalam Pengajian dan Bimbingan Belajar di Madrasah Diniyah dengan Prestasi Belajar di Sekolah - Moh. Ali Aziz (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Correlation between Activities in Pengajian and Learning Guidance in a Religious School and Achievement in Schools. The study aimed to investigate the correlation between students' activities on pengajian and learning guidance in a religious school and learning achievement at their schools. The subjects were students in junior and senior high schools participating in religious schools. The data were collected through questionnaire, interview, and documentation. The result revealed that there was a positive correlation between students' activities in the religious school and their learning achievement in the school. The determinat factors were religious motivation and cooperative learning method applied in the religious school.